Use of whole-genome sequencing to detect an outbreak of Malassezia pachydermatis infection and colonization in a neonatal intensive care unit—California, 2015–2016. (6th July 2020) - Chow, Nancy A.; Chinn, Raymond; Pong, Alice; Schultz, Kerry; Kim, Janice; Gade, Lalitha; Jackson, Brendan R.; Beer, Karlyn D.; Litvintseva, Anastasia P.
Abstract: Whole-genome sequencing confirmed the presence of a Malassezia pachydermatis outbreak among neonates in a neonatal intensive care unit. This technology supports the importance of adhering to infection prevention measures.